SCDT-27. CHILDREN'S BRAIN TUMOUR DRUG DELIVERY CONSORTIUM. (6th November 2017) - Rahman, Ruman; Grundy, Richard; Campbell, Emma; Brem, Henry; Pearl, Monica; Green, Jordan; Janowski, Miroslaw; Cohen, Kenneth; Walczak, Piotr; Warren, Katherine; Lowis, Stephen; Mullen, Alexander; et al.
Abstract: INTRODUCTION: Whilst there is an urgent need to expedite the development of new or repurposed drugs for children's cancer, the additional challenge in the developing brain is to ensure the drug is delivered to the tumour at therapeutic and non-toxic concentrations for sufficient duration to achieve the biological effect. This is the necessary focus for personalised medicine agendas in children's brain tumours as they account for over 20% of childhood cancers and differ significantly in their biological characteristics from their adult counterparts. METHODS: The authors took part in an international CNS drug delivery London workshop funded by the charity Children with Cancer UK in February 2016, where different experimental techniques aimed at optimising CNS drug delivery in children's brain tumours were presented and discussed. RESULTS: The workshop was reported and promoted through e-cancer (http://ecancer.org/journal/10/full/630-highlights-of-children-with-cancer-uk-s-workshop-on-drug-delivery-in-paediatric-brain-tumours.php ; http://ecancer.org/conference/831-drug-delivery-in-paediatric-brain-tumours.php ). We were encouraged to develop a proposal to establish an international research consortium to raise awareness and promote collaboration in the field. This is now funded for two years by Children with Cancer UK. The Children's Brain Tumour Drug Delivery Consortium seeks to strengthen collaborative developments by working closely with the international children's brain tumour community, encouraging and facilitating discussions between an international, multi-disciplinary network of clinicians and researchers within pharma and academia as well as a range of funders and stakeholders. As of July 2017, we have 77 individuals from 10 nations registered as members, with diverse stakeholders represented by academics, clinical academics, charities, public/patient groups, industry and regulatory bodies. CONCLUSION: We present this abstract to the SNO-SCIDOT conference to launch this initiative in America, inviting collaborators to promote this research priority for children across the world and to consider joining the consortium, which will be presented at the conference.